2010
DOI: 10.1016/j.visres.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Covert spatial attention in search for the location of a color-afterimage patch speeds up its decay from awareness: Introducing a method useful for the study of neural correlates of visual awareness

Abstract: Previous research has reported that attention to color afterimages speeds up their decay. However, the inducing stimuli in these studies have been overlapping, thereby implying that they involved overlapping receptive fields of the responsible neurons. As a result it is difficult to interpret the effect of focusing attention on a phenomenally projected target-afterimage. Here, we present a method free from these shortcomings. In searching for a target-afterimage patch among spatially separate alternatives the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…Voluntary covert attention to color afterimage, afterimage of spatially modulated contrast, or spatially localized motion aftereffect tends to speed up their decay from awareness (Lou, 2001; Suzuki and Grabowecki, 2003; Wede and Francis, 2007; Bachmann and Murd, 2010; van Boxtel et al, 2010a; Murd and Bachmann, 2011). Sixth, some aspects of a scene such as the gist or animated objects can be explicitly noticed without attention and without compromising the competing focused attention task (van Boxtel et al, 2010b; see, however, Cohen et al, 2011).…”
Section: Why It Can Be Said That Attention Is Not the Basis For Conscmentioning
confidence: 99%
See 1 more Smart Citation
“…Voluntary covert attention to color afterimage, afterimage of spatially modulated contrast, or spatially localized motion aftereffect tends to speed up their decay from awareness (Lou, 2001; Suzuki and Grabowecki, 2003; Wede and Francis, 2007; Bachmann and Murd, 2010; van Boxtel et al, 2010a; Murd and Bachmann, 2011). Sixth, some aspects of a scene such as the gist or animated objects can be explicitly noticed without attention and without compromising the competing focused attention task (van Boxtel et al, 2010b; see, however, Cohen et al, 2011).…”
Section: Why It Can Be Said That Attention Is Not the Basis For Conscmentioning
confidence: 99%
“…Thus it is a logical option to consider a mechanism dedicated to producing the changes in the processed contents so that they become explicitly experienced, a mechanism in addition to the listed ones. While often this function has been given to the attention mechanisms, the facts that attention is either independent of, insufficient for, or works against target information awareness (Hardcastle, 1997; Lou, 2001; Lamme, 2003; Koch and Tsuchiya, 2007; van Gaal and Fahrenfort, 2008; Wilimzig et al, 2008; Tsuchiya and Koch, 2009; Bachmann and Murd, 2010; Brascamp et al, 2010; van Boxtel et al, 2010a,b; Carlson et al, 2011; Hsu et al, 2011; Kaunitz et al, 2011; Lathrop et al, 2011; Morgan, 2011; Murd and Bachmann, 2011; Shin et al, 2011; Watanabe et al, 2011) suggest the need for a specialized consciousness mechanism. (This standpoint is even more strengthened by sound arguments about the non-existence of attention – Anderson, 2011).…”
Section: Why the Controversy Over The Attention Versus Consciousness mentioning
confidence: 99%
“…For example, subliminally presented visual stimuli, that is, stimuli below the threshold of visual awareness, can capture attention in a stimulus-driven or goal-directed way, without eliciting participants’ awareness of these stimuli itself (e.g., Kentridge et al, 1999 , 2004 ; Scharlau and Ansorge, 2003 ; Ansorge et al, 2009 , 2010 ; Schöberl et al, 2015 ). In addition, elective attention can speed up fading of stimulus-related sensory experience (e.g., Bachmann and Murd, 2010 ; Murd and Bachmann, 2011 ), which speaks against attention as the sole or even the main cause of awareness.…”
Section: Introductionmentioning
confidence: 99%
“…However, several recent studies have shown that attention has a detrimental effect on the duration of afterimages or sensory aftereffects (Lou, 2001; Bachmann and Murd, 2010; van Boxtel et al, 2010). If attention readily eliminates phenomenal experience then the awareness-related mechanisms whose activity is suppressed together with phenomenal experience must be independent from the attentional mechanisms.…”
mentioning
confidence: 99%